Legal Construction of Consanguineous Marriages (Analysis of Article 8 of Law Number 1 of 1974 concerning Marriage) - Ryan Ade Saputra; Haris Sanjaya, Umar (Faculty of Law Hang Tuah University, 2023)
Inbreeding is an act that violates the law, both marriage law in Indonesia and religious law. As Article 8 of Law Number 1 of 1974 regulates that marriage is prohibited. The main problem to be discussed is related to the legal construction of inbreeding and the analysis of inbreeding based on Legislation of Marriage. This research is normative research using statutory, case and concept approaches. This research shows that there are people who want to end consanguineous marriages through divorce. Meanwhile, consanguineous marriages are marriages that do not meet the requirements for a marriage to be valid, so they must be annulled. The advice from this research is that if someone knows that there is a sibling relationship with the person they are going to marry, then they should not proceed with the marriage. However, if you have already entered into a marriage, the marriage must be annulled. Apart from that, if you are going to get married, you have to do more research regarding the relationship of each couple. This includes registering marriages to prevent marriages between people who are related by blood.